ANALISIS HUKUM ASAS PENCEMAR MEMBAYAR SEBAGAI TANGGUNG JAWAB KORPORASI DALAM TINDAK PIDANA LINGKUNGAN - Lisa Tumilantouw, Ursula; Junita Melo, Isye; Leonardo Lombok, Lesza (At-Tanwir Law Review, 2025)
One of the principles that deserves serious attention in environmental law enforcement is the "polluter pays principle," which means that any business actor whose activities cause environmental pollution and/or damage is obligated to bear the full cost of its restoration. However, many courts in Indonesia have yet to apply this principle firmly in various cases. Therefore, this research aims to comprehensively explain the regulation of the polluter pays principle in Indonesian legislation and its implementation in environmental cases. Using a normative legal research method, the author finds that the polluter pays principle is explicitly regulated in various environmental laws in Indonesia, particularly in Law No. 32 of 2009. For corporations, the implementation of this principle includes legal responsibility for environmental damage, the internalization of environmental costs into production processes, and the provision of guarantee funds. However, its enforcement remains weak, as illustrated by the case of mangrove destruction in the Bunaken National Park, where the imposed fine was too low and not accompanied by a restoration obligation, thus failing to provide a sufficient deterrent effect.